Élite e democrazia: una «promessa mantenuta»? - Bonichi, Franca (SocietàMutamentoPolitica, 2017)
Through the contribution of classical and contemporary authors, Political Sociology offers an important opportunity to reflect on the crisis affecting democracy today. Crucial is the relationship between elites and democracy and particularly the theory of democratic elitism, a paradigm that has been considered the main source of democratic legitimacy in the Western world for decades. Cornerstones of this paradigm are the competence and representativeness of the elites. Through the analysis of some of its exponents, Political Sociology gives us the instruments to process these prerogatives/functions and to use them as parameters in defining the quality of the democratic participation.